2022
DOI: 10.3390/su14148349
|View full text |Cite
|
Sign up to set email alerts
|

Water Sustainability in the Context of Global Warming: A Bibliometric Analysis

Abstract: Sustainable water use is becoming a key problem in the present time, since global warming is having a strong impact on usable water resources. This study aims to provide a systematic bibliometric analysis on water sustainability in the context of global warming, in order to provide a clearer view on the existing research trends and to find eventual gaps in research that can be exploited in the future. The selection and analysis of the most relevant papers discussing the chosen topic pointed out a strong increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…As the Brundtland Commission concluded that the fundamental concepts in policy generation are "sustainability" and "sustainable development", the new common goal has become "development that meets the needs of the present without compromising the ability of future generations to meet their own needs" [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…As the Brundtland Commission concluded that the fundamental concepts in policy generation are "sustainability" and "sustainable development", the new common goal has become "development that meets the needs of the present without compromising the ability of future generations to meet their own needs" [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The main weaknesses are that the focus of a large majority of the studies is on present problems and not on future challenges and reliable solutions for them. Importantly, there is also an almost complete lack of research about the role of conserving natural habitats or of re-naturalization, as well as a relative low number of studies including cultural aspects in addressing water sustainability issues [8].…”
mentioning
confidence: 99%